2014
DOI: 10.1186/1471-2407-14-598
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine modulates breast cancer metastasis to the brain in a murine model

Abstract: BackgroundDespite advances in the treatment of primary breast tumors, the outcome of metastatic breast cancer remains dismal. Brain metastases present a particularly difficult therapeutic target due to the “sanctuary” status of the brain, with resulting inability of most chemotherapeutic agents to effectively eliminate cancer cells in the brain parenchyma. A large number of breast cancer patients receive various neuroactive drugs to combat complications of systemic anti-tumor therapies and to treat concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 53 publications
2
34
0
1
Order By: Relevance
“…In contrast to these findings, mRNA expression of TNF-α, IL-1α, IL-1β, and intercellular adhesion molecule-1 (ICAM-1) was increased in vivo using polymerase chain reaction (PCR) analysis and may affect the BBB permeability [14]. However, a double-blind study in human subjects found no association between cytokine levels IL-6, IL-8, IL-10, TNF-α, and IL-1ra and escitalopram use [301].…”
Section: Antidepressants Affect the Neuroinflammatory Environmentmentioning
confidence: 88%
See 4 more Smart Citations
“…In contrast to these findings, mRNA expression of TNF-α, IL-1α, IL-1β, and intercellular adhesion molecule-1 (ICAM-1) was increased in vivo using polymerase chain reaction (PCR) analysis and may affect the BBB permeability [14]. However, a double-blind study in human subjects found no association between cytokine levels IL-6, IL-8, IL-10, TNF-α, and IL-1ra and escitalopram use [301].…”
Section: Antidepressants Affect the Neuroinflammatory Environmentmentioning
confidence: 88%
“…Also suspected as a risk factor for brain metastasis by Shapovalov et al [14] is antidepressant use.…”
Section: Risk Factorsmentioning
confidence: 97%
See 3 more Smart Citations